Basin evolution and petroleum prospectivity of the continental margins of India - Bastia, R. (Rabi); Radhakrishna, M.; ScienceDirect eBooks (Oxford : Elsevier, 2012)
During the past 10 years, the Oil industry in India has seen a tremendous rise in exploration activity with several major E & P companies generating vast amount of new geological and geophysical data. The availability of such integrated data sets (gravity, magnetic, seismic, drilled wells), especially in the deep offshore basins, has led the authors to revisit earlier concepts and models in order to redefine the tectonic framework of major offshore basins along the Indian continental margins. The book covers the stratigraphic evolution, play types and the classification of major offshore basins both in shallow and deepwater environments. Features: * Incorporation of latest dataset (specially the seismic, gravity and magnetic) * Analogy of global offshore basins with India * Sedimentation and depositional history of Bengal fan and Indus fan * Redefinition of major tectonic framework of the margins * Exceleent high quality graphics that include: seismic sections, gravity-magnetic maps, conceptual geological models and new revised tectonic elements Benefits: * Comprehensive geological and geophysical demonstration of basin development and history in the light of petroleum prospectivity of the Continental Margins of India * Emerging concepts on rift-drift history of the Eastern Gondwanaland in the light of probable Mesozoic prospects hitherto little known in this part of the world * A deep insight of all major offshore prospective basins with illustrations and high resolution datasets otherwise not available to common readers * Useful as a textbook for petroleum professionals and as a reference book for marine geo-science researchers.
Elsevier
Keywords: Petroleum -- Prospecting -- Indian Ocean; Petroleum -- Geology -- Indian Ocean; Petroleum -- Geology; Petroleum -- Prospecting; Indian Ocean; Electronic books